Building a Sustainable Educational Institution: an Analysis Study of Social Responsibility and Ethics in Strategic Management at MTsN 8 Tulungagung - Suyoko; Sulistyorini; Agus Zaenul Fitri (CV. Gerasi Insan Nusantara, 2026)
The sustainable development of educational institutions is crucial to produce students who are not only academically intelligent but also possess strong character and a sense of social responsibility. This study examines the application of Social Responsibility and Ethics at MTsN 8 Tulungagung, with a focus on the implementation of the Compassion-Based Curriculum. Its implementation in areas with limited facilities, such as MTsN 8 Tulungagung, faces various challenges that need to be managed properly. This study aims to apply the application of social responsibility and ethics in educational management in the context of the implementation of CBC. This research methodology uses a qualitative approach with a descriptive case study. Data were collected through in-depth interviews, participant observation, and document analysis to educational management policies and practices at MTsN 8 Tulungagung. The results show there are has successfully integrated ethical values and social responsibility into educational management, despite facing limited resources. Through the implementation of the CBC, this school focuses not only on academic achievement but also on character development of students who care for others. The application of Islamic ethics and social responsibility at the school management level, both in decision-making and daily interactions, creates a more humanistic and sustainable educational.